On the taxonomy of the genus Sidonis Mulsant, stat. nov. (Coleoptera: Coccinellidae: Chnoodini) with descriptions of new species from Brazil - Churata-Salcedo, Julissa M.; Almeida, Lucia M.; González, Guillermo; Gordon, Robert D. (Zootaxa, 2017)
The subgenus Sidonis Mulsant, 1850 is elevated to generic status and two new species from Brazil are described and illustrated: Sidonis bira sp. nov. and Sidonis biguttata sp. nov. New geographic distribution records are provided. In addition, lectotypes of Sidonis consanguinea (Mulsant, 1850) and S. guttata (Sicard, 1912) are designated. Illustrations of diagnostic characters from five of six species of the genus, comments on the differences from similar species and a key to all recognized taxa are included.